Customer orientation, value creation and economic sustainability of fast moving consumer goods' firms in Lagos State, Nigeria - Adeola Elizabeth Adetayo; Michael Segun Ogunmuyiwa; Oludayo Olajide Ariyo (Economic Review: Journal of Economics and Business, 2024)
The importance of customer orientation and value creation on economic sustainability is well established in the literature. However, studies on customer orientation and value creation majorly focused on performance of Smal and Medium Enterprises (SMEs) and the banking sector. Instead, this study focused on Fast Moving Consumer Goods (FMCG) Firms and employed a survey research design through the use of a structured questionnaire as an instrument of data collection. Two hundred and fifteen (215) sales and marketing staff among FMCG firms in Lagos State, Nigeria constituted the sample size using purposive sampling technique. The empirical results revealed that: customer orientation and value creation individually and jointly have positive and significant effect on the economic sustainability among FMCG firms in Lagos State, Nigeria. The study concluded that customer orientation and value creation exert strong influence on economic sustainability of FMCG firms in Lagos State, Nigeria. It is recommended that FMCG firms in Lagos State should cultivate a strong relationship with their customers by prioritizing their requirements (needs) and desires. The study also recommended the need for persistence in creating customer value to foster long term relationships. and achieve competitive advantage as well as improve their economic sustainability.
Keywords: M31; L25; L60; L67; 330; customer orientation; value creation; competitive advantage and economic sustainability